Servicio de obreros de alquiler en la ciudad de Babahoyo - Palma Ronquillo, Robinson Efraín (2020)
The reason why the idea of creating this venture arose was to see that there are too many university students with a degree and cannot exercise their career for reasons that do not have a job because there are more and more requirements and it is difficult for them to access or people They have empirical knowledge, but they cannot exercise their wisdom because they do not have a degree or because they are older and they do not hire them because for many companies they have already completed their work cycle. Through an exhaustive investigation, it was found that there is a strong demand for jobs such as plumbing, electricity, mechanics, technical service, masonry, remodeling, among others. In order to carry out this investigation, a survey was carried out, conducting a market study in order to verify what impact this venture will have on the market in the city of Babahoyo. To conclude, a rental worker has an innovative and striking proposal that is based on being able to raise the employment rate, favoring all university students and people who do not have a job, and in turn improving the quality of life of families, especially all the women who are responsible for supporting their homes